Recognition of prior learning in promoting lifelong learning: A pedagogy of hope or a shattering of dreams? - Frick, L; Albertyn, R (South African Journal of Higher Education, 2011)
Recognition of prior learning (RPL) is an issue within the context of lifelong learning, given the (South African) issues of equity and redress, the international demands on adults to contribute to the knowledge economy, qualification inflation and increased competitiveness for knowledge workers. In the process of conscientisation and in an attempt to provide a pedagogy of hope, education could be seen by some as the panacea of all ills and RPL clearly needs to be handled with circumspection. RPL needs to be implemented ethically for it to be sustainable and to make a contribution to the individual perceptions and attainment of the Pedagogy of Hope. Integrating RPL has resulted in varied approaches: RPL can be aimed at the selection of individuals and the recognition of existing knowledge; or the transformation of individuals or knowledge in the process of assessment. This differentiation provides a useful distinction between the various functions that RPL can fulfill. In this chapter we intend to explore the potential that RPL holds as a pedagogy of hope specifically within the field of lifelong learning. We argue that the practice of RPL may facilitate or inhibit hope for adult learners in higher education.